TINJAUAN YURIDIS PENGISIAN KEKOSONGAN JABATAN WAKIL KEPALA DAERAH DALAM SISTEM KETATANEGARAAN INDONESIA - Nurhakim, Yori Imam; Firdaus, Emilda; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The position of the deputy regional head in Indonesia is not actually statedand stated clearly in the constitution, but in normative juridical terms the positionof the deputy regional head in Indonesia can be seen from Article 66 paragraph(1) of the law on regional government number 23 of 2014.The main problem in this research is regarding the vacancy of the deputygovernor, and the vacancy of the deputy regent which creates political intereststhat clearly show that the elite is not taking sides with the broad public benefit.The vacant positions of Deputy Governor, Deputy Regent and Deputy Mayor willbe filled if the remaining term of office is more than 18 (eighteen) months from thevacancy of the position.This research is normative legal research. This is based on libraryresearch which takes quotations from reading books, or supporting books that arerelated to the problem to be researched. This research uses secondary datasources consisting of primary, secondary and tertiary book materials. Thisresearch also uses qualitative data analysis and produces descriptive data.From the results of the research and discussions carried out, severalconclusions were obtained, namely: First, the procedures for filling vacancies fordeputy regional heads who come from political parties and combinations ofpolitical parties in this context give rise to multiple interpretations. Therefore theauthor conducted this research. Second, there are several efforts that thegovernment can take, namely normative juridically in Law Number 10 of 2016Regarding the Second Amendment to Law Number 1 of 2015 concerning theStipulation of Government Regulations in Lieu of Law Number 1 of 2014concerning the Election of Governors, Regents and Mayors into Law, precisely inthe provisions of Article 176 paragraph (4) requires the filling of vacant positionsdeputy regional heads who still have more than 18 (eighteen) months remaining inoffice.Keywords: Juridical Review-Filling the Position of Deputy Regional Head.